2022
DOI: 10.1038/s41380-021-01404-7
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal acetylcholine modulates stress-related behaviors independent of specific cholinergic inputs

Abstract: Acetylcholine (ACh) levels are elevated in actively depressed subjects. Conversely, antagonism of either nicotinic or muscarinic ACh receptors can have antidepressant effects in humans and decrease stress-relevant behaviors in rodents. Consistent with a role for ACh in mediating maladaptive responses to stress, brain ACh levels increase in response to stressful challenges, whereas systemically blocking acetylcholinesterase (AChE, the primary ACh degradative enzyme) elicits depression-like symptoms in human sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…[ 33 ] Stimulation of MS‐DG cholinergic pathway ameliorates the deficits of spatial memory. [ 34 ] Optogenetic stimulation of septohippocampal terminals or selective chemogenetic activation of acetylcholine‐positive inputs to hippocampus increases stress‐related behaviors, [ 35 ] however, to date, the function of MS‐DG pathway in depression is largely unknown. In the present study, we identified the MS‐DG pathway as a new circuit in regulating depressive‐like behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 ] Stimulation of MS‐DG cholinergic pathway ameliorates the deficits of spatial memory. [ 34 ] Optogenetic stimulation of septohippocampal terminals or selective chemogenetic activation of acetylcholine‐positive inputs to hippocampus increases stress‐related behaviors, [ 35 ] however, to date, the function of MS‐DG pathway in depression is largely unknown. In the present study, we identified the MS‐DG pathway as a new circuit in regulating depressive‐like behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of an acute stressor, cholinergic NBM neurons fire rapidly ( Zhang et al, 2004 ; Hangya et al, 2015 ). A variety of acute stressors stimulate NBM cholinergic neuron activity, including mild food shock, predator odor, and exposure to novel/stressful environments ( Jing et al, 2020 ; Rajebhosale et al, 2021 ; Mineur et al, 2022 ). NMB cholinergic neuron firing releases acetylcholine within the BLA and modulates attention, arousal, memory storage, reward processing, and threat-encoding ( Mark et al, 1996 ; Jing et al, 2020 ; Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This PBP-sensor exhibits rapid activation and decay kinetics at the millisecond level and is independent of most cholinergic drugs. in the vicinity of the indicator (Crouse et al, 2020;Jing et al, 2018Jing et al, , 2020Mineur, Mose, Maibom, et al, 2022;Mineur, Mose, Vanopdenbosch, et al, 2022).…”
Section: Electrochemical Techniques: Amperometry/ Voltammetrymentioning
confidence: 99%
“…The resulting fluorescence emission is then collected through the same fiber and detected by a sensitive photodetector. The intensity of the fluorescence signal is directly proportional to the concentration of the analyte (ACh, in this case) in the vicinity of the indicator (Crouse et al, 2020; Jing et al, 2018, 2020; Mineur, Mose, Maibom, et al, 2022; Mineur, Mose, Vanopdenbosch, et al, 2022).…”
Section: Techniques For Measuring Acetylcholine Levels In Brainmentioning
confidence: 99%
See 1 more Smart Citation